Social Entrepreneurial Orientation and Performance of Third Sector Organizations in South-East, Nigeria - Paul Justice Adum; Ann I. Ogbo; Madu Ikemefuna; Okechi Anthony Obiora (Rowter Journal, 2024)
The study focused on social entrepreneurial orientation and performance of third sector organizations. This study made use of the descriptive cross-sectional research design. The study’s interest is the third-sector organizations that are operational in the South East region of Nigeria. The study applied simple random sampling technique to select 400 participants. Descriptive statistics was used to determine the mean, standard deviation, and inter-item correlation. The analysis was carried out using Multiple Regression. The regression includes Hannan-Quinn criterion, F-statistic, and Durbin-Watson statistic. Satorra-Bentler Test was employed to spot issues of homoscedasticity. Findings showed that effectual orientation has significant positive effect on social performance and commercial performance of third-sector organizations. Finding further revealed that social mission orientation does not significantly relate with social performance of third-sector organizations, and that social mission orientation has no significant negative linear relationship between commercial performance. The study recommended among others that third-sector organizations should prioritize the adoption of effectual orientation as a core strategic approach, and should re-evaluate their operational strategies to ensure that the stated social missions are effectively translated into tangible, measurable actions that align with the needs and expectations of the communities served.